(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Age-related macular degeneration (AMD) comprises 12.5% and 22% in the structure of ocular incapacitation among persons of working and pension age, respectively. The important role in the pathogenesis of AMD belongs to ocular hemodynamics disorders. The lack of efficacy of a therapy for AMD determines the need to search for new drugs which would improve ocular hemodynamics in the disease. Purpose. To study the effect of phosphocreatine on ocular hemodynamics and the functional state of the macular area in patients with dry age-related macular degeneration. Material and Methods. Twenty-three patients (36 eyes) comprised Study group in which a complex therapy included phosphocreatine as a Neoton drug, in a dose of 1 g diluted in 50 ml of 0.9% sodium chloride, for 8 days. Twenty-five patients (39 eyes), comprising Control group, did not receive phosphocreatine in their treatment. Each patient was performed ultrasonic Doppler examination of the ophthalmic artery and a photostress test. Results. After treatment, the values of Doppler examination and photostress test were improved only in patients of Study group. Maximal and minimal blood flow velocity in the ophthalmic artery increased by 29% and 30%, respectively; vascular resistance index decreased by 14%; and photostress recovery time decreased by 33%. These indices did not change significantly in Control group patients. Conclusions. Inclusion of the phosphocreatine-containing drug in the complex therapy for the patients with dry AMD corrects ocular hemodynamics disorders, improves the functional state of the macular area and improves treatment outcomes.